2020
DOI: 10.1039/d0nr05210h
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon active nucleus-targeting carbon dots: enhanced ROS generation and photodynamic therapy for oral cancer

Abstract: Novel conjugated carbon dots (CDs) were synthesized as two-photon active photosensitisers to unleash lethal reactive oxygen species (ROS) for nucleus targeting photodynamic therapy (PDT). To enhance therapeutic efficiency and preclude...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 23 publications
0
54
0
Order By: Relevance
“…Several papers have reported that targeting using folic acid receptors does not seem to have a significant effect on increasing phototoxicity [47]. However, many studies have reported that active targeting using folic acid ligands increases phototoxicity [48][49][50]. In this study, FA-conjugated FA-PEAH-UCNPs-Pha showed higher phototoxicity than free Pha and CH3-PEAH-UCNPs-Pha, possibly due to improved cellular uptake by the FA receptor-medicated endocytosis process.…”
Section: In Vitro Phototoxicity Of Ucnp-based Nanocarriersmentioning
confidence: 58%
“…Several papers have reported that targeting using folic acid receptors does not seem to have a significant effect on increasing phototoxicity [47]. However, many studies have reported that active targeting using folic acid ligands increases phototoxicity [48][49][50]. In this study, FA-conjugated FA-PEAH-UCNPs-Pha showed higher phototoxicity than free Pha and CH3-PEAH-UCNPs-Pha, possibly due to improved cellular uptake by the FA receptor-medicated endocytosis process.…”
Section: In Vitro Phototoxicity Of Ucnp-based Nanocarriersmentioning
confidence: 58%
“…Biomaterial-mediated photodynamic therapy. PDT 18,56 relies on photosensitizers to generate ROS under irradiation with external light at a specific wavelength to kill tumours. Since maxillofacial tumours usually occur in areas with easy access to light irradiation, PDT can be conveniently implemented.…”
Section: Biomaterial-mediated Chemotherapymentioning
confidence: 99%
“…Moreover, two-photon active photosensitizers that release lethal ROS for nucleus-targeting PDT were also proven feasible in oral cancer therapy. Nasrin et al 56 fabricated novel conjugated carbon dots (CDs) combined with curcumin and folic acid to enhance internalization; accordingly, elevated cancer cell destruction was observed via a direct attack on DNA. In addition to carbon dots, iron oxide nanoparticles show potential for PDT; additionally, their imaging capacity is worth studying.…”
Section: Biomaterial-mediated Chemotherapymentioning
confidence: 99%
“…The ROS HO• can synergize the chemotherapy by a cascade of bioreactions ( Figure 9 ). In addition, PDT is a promising clinical cancer treatment strategy, and it is also a common means of increasing ROS content and enhancing ROS-induced anticancer strategy [ 88 , 89 , 90 , 91 , 92 ]. PDT converts O 2 into ROS by light-activated PSs, while CDT generates cytotoxic •OH by an in situ Fenton or Fenton-like reaction between H 2 O 2 and catalysts [ 93 , 94 ].…”
Section: Activated Cascade Reactions To Enhance Ros-induced Cancer Therapymentioning
confidence: 99%